2022-RA-670-ESGO Age limits of mammography screening – a decision-analytic evaluation of the benefit-harm balance to inform decision making for the German screening context. (20th October 2022) - Sroczynski, Gaby; Hallsson, Lára Rún; Mühlberger, Nikolai; Kühne, Felicitas; Jahn, Beate; Kölsch, Heike; Sauerland, Stefan; Angelescu, Konstanze; Siebert, Uwe
Abstract : Introduction/Background: We aimed to evaluate the long-term benefits and harms of various breast cancer (BC) screening strategies including mammography with an earlier start and/or later stop than the current biennial BC screening age 50–69 years in Germany using a decision-analytic model for evidence synthesis. Methodology: We developed a Markov-state-transition model simulating BC progression including ductal carcinoma in situ (DCIS) to evaluate various screening strategies differing by age at start and end of screening and by screening interval. International data for mammography accuracy along with German epidemiologic, clinical data and age-specific quality-of-life (QoL) data were used. Outcomes included detected DCIS and invasive BC, BC-related deaths, life years LY), and quality-adjusted LY (QALY), number of positive, false-positive, and total mammograms, overdiagnosis, and the incremental harm-benefit ratio (IHBR). Comprehensive sensitivity analyses were conducted. Results: In the base-case analysis, the highest potential gain in LY was achieved with mammography at age 45–79 (annual, age 45–49 y; biennial, 50–79 y) with 10.0 LY gained (LYG) per 100 participating women compared with current screening. The highest gain in QALYs is expected by biennial mammography at ages 45–74 (3.5 QALYs gained/100 women vs. current screening). Considering potential burden associated with additional mammograms, lowering the start age to 45 years (biennial, age 45–69 y) has an IHBR of 47 additional mammograms/LYG (vs. current screening). Compared to this screening, biennial mammography at age 45–74 results in 96 additional mammograms/LYG. Extending biennial mammography to age 45–79 or additionally screen annually at age 45–49 results in substantially less favorable IHBRs. Overdiagnoses occurred mainly due to DCIS. Key results were robust in sensitivity analyses. Conclusion: Based on our results, extension of the starting and stopping age for mammography may prevent additional BC deaths and increase remaining life expectancy. Considering QoL, biennial screening from age 45 to 74 years may provide an acceptable benefit-harm balance.